2018
DOI: 10.1155/2018/3061084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Outcomes among Children with Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A 20-Year Study in a Tertiary Referral Hospital

Abstract: Aim To determine the probable causative factors, clinical features, and treatment outcomes of Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and SJS-TEN overlap in children. Methods A 20-year database review of all children diagnosed with SJS/TEN/SJS-TEN overlap at the King Chulalongkorn Memorial Hospital, Thailand. Results 36 patients (M : F, 16 : 20) with the mean age of 9.2 ± 4.0 years were identified. There were 20 cases of SJS, 4 cases of SJS-TEN overlap, and 12 cases of TEN. Drugs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
2
24
0
6
Order By: Relevance
“…In our case series of paediatric patients only two, both with TEN, required intensive care and none died, confirming that mortality rate from SCARs is higher in adults than in children, probably because of different immunological response and comorbidity of chronic diseases that are rare in paediatric patients.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In our case series of paediatric patients only two, both with TEN, required intensive care and none died, confirming that mortality rate from SCARs is higher in adults than in children, probably because of different immunological response and comorbidity of chronic diseases that are rare in paediatric patients.…”
Section: Discussionsupporting
confidence: 74%
“…This association was successful, as our children suffered no sequelae after overcoming the acute phase. Almost all the paediatric studies on SJS/TEN have reported that CS, alone or in combination with IVIg, are the most important treatments, in addition to antimicrobics and supportive care, to ensure a low mortality rate and the use of CS does not seem to associate with an increased risk of infections …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients presented with morbilliform rash (83.3%), blisters (38.9%), targetoid lesions (25.0%), and purpuric macules (2.8%), and the most common mucosal involvements were oral (97.2%) and eye mucosae (83.3%). 9 Lesions in this patient's mucosae followed the same order as those reported in the literature, starting at the oropharynx, and spreading to the ocular, genital, and anal mucosae. 10 In 2000 was published an article with a toxic epidermal necrolysis-specific severity-of-illness score for adults le to predict prognosis for the epidermal necrolytic disorders, called SCORTEN.…”
Section: Discussionsupporting
confidence: 69%